THE IMPACT OF THE MERDEKA BELAJAR KAMPUS MERDEKA PROGRAM AND MICRO, SMALL, AND MEDIUM ENTERPRISES ASSISTANCE ON THE INTEREST OF ENTREPRENEURS IN BATCH 4th KAMPUS MENGAJAR PARTICIPANTS INDONESIA - Sirait, Pretty Elfrida (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
The impact of covid-19 has made the country's economy experience a slump. Goverment has launched one big movement in Indonesia called MBKM (Merdeka Belajar Kampus Merdeka) . MBKM means free for learn and freedom for college, MBKM contains several sub programs for Indonesia Students such as Kampus Mengajar. The purpose of this study was to determine whether or not there was an Impact MBKM on the entrepreneurial interest of Kampus Mengajar 4th participants throughout Indonesia, to determine whether or not there was an Impact of MSMES assistance on the entrepreneurial interest of Kampus Mengajar 4th participants throughout Indonesia, to determine the types of businesses that many Interested college students teaching 4th throughout Indonesia, to find out students' views on the MBKM program which is in great demand by Kampus Mengajar 4th students, To find out the types of MSMEs that are interested by Kampus Mengajar 4th students in Indonesia. The research method used in this research is a descriptive quantitative research method by making Kampus Mengajar participants teaching 4th throughout Indonesia the object of research.